Process evaluation of a SOx and NOx exhaust gas cleaning concept for marine application - Ibrahim, Serwah (My University, 2016)
Maritime transport accounts for about 80% of all commercial cargo transport. The maritime sector is a large emitter of greenhouse gases, sulphur oxides, and nitrogen oxides. Since 1997, the International Maritime Organisation (IMO) set regulations (Marpol Annex VI) requiring maritime transport vessels to reduce exhaust emissions. Today vessels are required to fulfil stringent emission targets for SO2 (Regulation 14 in Annex VI) and for NOx (Regulation 13). A common method of reducing SO2 emissions is by absorption of exhaust gases derived from the marine diesel engine, through wet scrubbing while NOx is commonly reduced by SCR. Studies have shown that, under certain pH conditions and exhaust gas compositions, SO2 and NO2 can react in liquid phase to form stable compounds The objective of this work is to investigate a process for simultaneous absorption of SO2 and NO2. A steady-state simulation model is constructed in Aspen Plus, of a scrubber developed by Yara Marine Technology, which utilises the surrounding seawater in order to efficiently scrub SO2 from exhaust gases. The simulation was performed in a packed RateSep model, with two configurations: one open loop (once-through liquid stream) model, and one closed loop (recycled liquid stream) model. Parameter data from a real life case is used to construct the model, and operational data from the absorber is used to verify the model. The results show that the process removes NOx efficiently from the flue gas stream. There is also an overall improvement of the SO2 removal compared to today’s process. In open loop configuration, the formation nitrogen and sulphur is mainly bound as HADS. In the closed loop configuration, due to the recirculation, there is a risk of N2O formation that must be considered. The oxidation of the NO present in the flue gas requires an oxidizing agent. The process would requires around 119 kg ClO2/h or 180 kg H2O2/h in order to oxidise all NO. In summary, there is a potential in utilising oxidation of NO to NO2 combined with wet scrubbing in order to meet maritime regulations for both SO2 and NOx emissions, which can compete with the current combination of SCR and wet SO2 scrubbing.
Keywords: Energi; Hållbar utveckling; Energiteknik; Energy; Sustainable Development; Energy Engineering